Pengaruh Cara Pengeringan Gabah terhadap Mutu Fisik, Fisikokimia, dan Organoleptik Beras Varietas Unggul Padi - Jumali, Jumali; Handoko, Dody D; Indrasari, Siti Dewi (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2020)
Rice grain drying using sun radiation has its problem during the rainy season, due to low radiation intensity. Box dryer using gas as its source of energy had been developed to overcome the problem during the rainy season. This research was aimed to study the effect of drying methods on physical, physicochemical, and organoleptic quality of some improved rice varieties. Seed of five rice varieties, namely Ciherang, Inpari 30, Inpari 32 (white grain rice), Inpari 24 and Inpago 7 (red grain rice), were planted at Sukamandi Research Station, Indonesian Center for Rice Research, following the Integrated Crop Management approach. The rice crops were harvested when the grain had ripen optimally, threshed using a threshing machine and the grains were dried using a box type dryer and using the sun radiation. The milled rice was analyzed for their physical, physicochemical, and organoleptic quality. Results showed that the differences of drying methods, namely sun-drying and box drying, affected the physical quality of rice grain. Box dryer for Ciherang variety yielded higher percentage of unpolished milled rice and the head grain rice was slightly higher than that of sun-drying. However, drying methods did not affect the physicochemical and organoleptic quality of the cooked rice. Box dryer is considered suitable for rice grain drying during the rainy season.